Detection of SHOX gene aberrations in routine diagnostic practice and evaluation of phenotype scoring form effectiveness - Hirschfeldova, Katerina; Florianova, Martina; Kebrdlova, Vera; Urbanova, Marketa; Stekrova, Jitka (Journal of human genetics, 2017)
Heterozygous aberrations of SHOX gene have been reported to be responsible for Léri-Weill dyschondrosteosis (LWD) and small portion of idiopathic short stature. The study was established to assess effectiveness of using phenotype 'scoring form' in patients indicated for SHOX gene defect analysis. The submitted study is based on a retrospective group of 352 unrelated patients enrolled as a part of the routine diagnostic practice and analyzed for aberrations affecting the SHOX gene. All participants were scanned for deletion/duplication within the main pseudoautosomal region (PAR1) using the multiplex ligation-dependent probe amplification (MLPA) method. The phenotype 'scoring form' is used in our laboratory practice to preselect patients for subsequent mutation analysis of SHOX gene-coding sequences. The overall detection rate was 11.1% but there was a significant increase in frequency of SHOX gene defect positive with increasing achieved score (P<0.0001). The most frequent aberration was a causal deletion within PAR1. In three probands, MLPA analysis indicated a more complex rearrangement. Madelung deformity or co-occurrence of disproportionate short stature, short forearm and muscular hypertrophy had represented the most potent markers to determine the likelihood of SHOX gene defect detection. We conclude that appliance of phenotype 'scoring form' had saved excessive sample analysis and enabled effective routine diagnostic testing.
Keywords: Osteochondrodysplasias; Humans; nanismus; mutační analýza DNA; techniky amplifikace nukleových kyselin; tělesná výška; Phenotype; Multiplex Polymerase Chain Reaction; lidé; Sequence Deletion; Homeodomain Proteins; osteochondrodysplazie; multiplexová polymerázová řetězová reakce; Gene Duplication; Dwarfism; Short Stature Homeobox Protein; DNA Mutational Analysis; poruchy růstu; duplikace genu; sekvenční delece; Growth Disorders; Body Height; Retrospective Studies; protein SHOX; fenotyp; homeodoménové proteiny; Nucleic Acid Amplification Techniques; genetické testování; retrospektivní studie; Genetic Testing